Full field vibration measurements on a cantilever beam under impact using visible and infrared deflectometry. (1st December 2021) - Robin, Olivier; O'Donoughue, Patrick; Berry, Alain; Farley, Vincent; Prithipaul, Kishan
Abstract: This paper reports results of full field vibration measurements conducted on a laboratory test case, a cantilever beam, submitted to a transient excitation using an impact hammer. The deflectometry technique in the visible and in the infrared spectra are employed to measure the beam's vibration field using high-speed cameras. The respective performances and implementations of both techniques, as well as potential applications, are discussed.